Faktor – Faktor yang Mempengaruhi Minat Nasabah terhadap Produk Gadai Emas pada PT Bank Syariah Indonesia KCP Medan Setia Budi - Inggit Eka Saputri (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Pawn gold is a loan facility with a gold guarantee to obtain cash with a high estimate, low and easy costs, can be automatically extended, stored safely and insured online or offline services. This study aims to find out what are the factors that influence customer interest in gold pawning products. The marketing mix in this research is location, promotion and service. With this type of qualitative research using descriptive methods, the results show that the three marketing mix of pawning gold promotions are the most dominant in influencing customer interest in pawning gold products. Keywords: pawn gold, Islamic banking